2019
DOI: 10.1007/s13202-019-0737-3
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation to assess the effectiveness of inhibitive nano-water-based drilling fluids for Zubair shale formation

Abstract: While drilling through shale formations, shale hydration, including shale swelling and dispersion, is frequently reported as the main wellbore instability problems, particularly when conventional drilling fluids (water-based) are used. These problems have many adverse effects on the drilling operations resulting in non-productive time. Nanoparticles have been recently introduced as a unique alternative to improve the performance of water-based drilling fluids for shale applications. This paper presents an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…According to research, drilling fluid properties can be significantly impacted by nanoclays, including nano-titanium, nano-copper oxide, nano-alumina, and nano-bentonite. Research has indicated that they can decrease permeability, regulate filtration characteristics, improve the mechanical qualities of the drilling fluid, and strengthen shale stability [53][54][55]. Additionally, nanoclays are a promising addition for a variety of drilling operations, including those in sensitive environments, as they can help improve the rheological behavior of the drilling mud and reduce fluid loss.…”
Section: Nanoclaymentioning
confidence: 99%
“…According to research, drilling fluid properties can be significantly impacted by nanoclays, including nano-titanium, nano-copper oxide, nano-alumina, and nano-bentonite. Research has indicated that they can decrease permeability, regulate filtration characteristics, improve the mechanical qualities of the drilling fluid, and strengthen shale stability [53][54][55]. Additionally, nanoclays are a promising addition for a variety of drilling operations, including those in sensitive environments, as they can help improve the rheological behavior of the drilling mud and reduce fluid loss.…”
Section: Nanoclaymentioning
confidence: 99%
“…Thus, in natural heterogeneous reservoirs, where it is not intuitively obvious how reactivity and transport are coupled, it is helpful to contextualize the stages of the fracturing process in this dimensionless framework. At present, the majority of shale reactivity studies are conducted under laboratory conditions including batch reaction and flow-through tests of core material. A present challenge faced in the field is the linkage of these data to reservoir-scale behavior through such nondimensionalized parametrization. In what follows, we review the steps of the fracturing process, while offering a contextualization of the Pe and Da associated with each step using local conditions of reactivity and characteristic length.…”
Section: The Hydraulic Fracturing Processmentioning
confidence: 99%
“…While addressing the drilling operations in extreme conditions, suitable additives are required to use in WBDF to avoid decomposition and better performance of the drilling fluids during drilling process. Nevertheless, due to the current advances in technology, novel nanocomposites have been selected to utilize as additives for modification of rheological properties as well as the filtration behavior of drilling fluids [ 87 ].…”
Section: Graphene Impacts In Drilling Operationsmentioning
confidence: 99%